2015
DOI: 10.1093/molbev/msv015
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Conserved Phylogenetic Core of Archaea Disentangles the Evolution of the Third Domain of Life

Abstract: Initial studies of the archaeal phylogeny relied mainly on the analysis of the RNA component of the small subunit of the ribosome (SSU rRNA). The resulting phylogenies have provided interesting but partial information on the evolutionary history of the third domain of life because SSU rRNA sequences do not contain enough phylogenetic signal to resolve all nodes of the archaeal tree. Thus, many relationships, and especially the most ancient ones, remained elusive. Moreover, SSU rRNA phylogenies can be heavily b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 80 publications
5
75
0
Order By: Relevance
“…In our study we could show that a complex endomembrane system does exist within Archaea—i.e., at least in I. hospitalis —supporting hypotheses that suggest an archaeal origin of the eukaryotic endomembrane system. This is in agreement with phylogenetic analyses that place Ignicoccus as a member of the TACK superphylym (Guy and Ettema, 2011), hypothesized to be a sister group of the recently described Asgard archaea and Eukaryotes (Lake et al, 1984; Cox et al, 2008; Foster et al, 2009; Kelly et al, 2011; Williams et al, 2012, 2013; Wolf et al, 2012; Yutin et al, 2012; Lasek-Nesselquist and Gogarten, 2013; Martijn and Ettema, 2013; Koonin and Yutin, 2014; Williams and Embley, 2014; Petitjean et al, 2015; Zaremba-Niedzwiedzka et al, 2017). In TACK archaea, several “eukaryotic signature proteins” (ESPs) are present including homologs to proteins that are involved in membrane remodeling processes in Eukaryotes (Guy and Ettema, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…In our study we could show that a complex endomembrane system does exist within Archaea—i.e., at least in I. hospitalis —supporting hypotheses that suggest an archaeal origin of the eukaryotic endomembrane system. This is in agreement with phylogenetic analyses that place Ignicoccus as a member of the TACK superphylym (Guy and Ettema, 2011), hypothesized to be a sister group of the recently described Asgard archaea and Eukaryotes (Lake et al, 1984; Cox et al, 2008; Foster et al, 2009; Kelly et al, 2011; Williams et al, 2012, 2013; Wolf et al, 2012; Yutin et al, 2012; Lasek-Nesselquist and Gogarten, 2013; Martijn and Ettema, 2013; Koonin and Yutin, 2014; Williams and Embley, 2014; Petitjean et al, 2015; Zaremba-Niedzwiedzka et al, 2017). In TACK archaea, several “eukaryotic signature proteins” (ESPs) are present including homologs to proteins that are involved in membrane remodeling processes in Eukaryotes (Guy and Ettema, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…This is showcased by the basal positions of M. kandleri and Thermotoga maritima within the archaeal and bacterial subtrees in Spang et al's (2015) trees (Figure  2 in [1]). M. kandleri is a fast-evolving archaeon and its basal position in most phylogenetic trees is now considered a technical artifact [33, 82]. Similarly, the examination of slow-evolving sites in rRNA sequences has revised the phylogenetic placement of T. maritima [83] (see also [84]).…”
Section: Technical Issues Related To Taxon and Character Sampling mentioning
confidence: 99%
“…Petitjean et al [6] identified 200 protein families, along with 57 ribosomal proteins and 14 RNA polymerase subunits, which represent 273 phylogenetic markers in 129 archaeal genomes. With this conserved core of archaeal genes, they inferred the phylogeny of the nodes of different orders with high robustness (statistical significance >95%).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the orders Methanopyrales, Methanobacteriales, and Methanococcales diverged around 3468 Ma ago, and methanogens class I or Methanomada appeared [6]. Later on, the order Thermoplasmatales diverged (3160 Ma ago), followed by the order Archaeoglobales (2799 Ma ago).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation